2019
DOI: 10.1515/geo-2019-0088
|View full text |Cite
|
Sign up to set email alerts
|

An integrated analysis of mineralogical and microstructural characteristics and petrophysical properties of carbonate rocks in the lower Indus Basin, Pakistan

Abstract: Carbonate rocks are believed to be proven hydrocarbon reservoirs and are found in various basins of Pakistan including Lower Indus Basin. The carbonate rock intervals of the Jakkher Group from Paleocene to Oligocene age are distributed in south-western part of Lower Indus Basin of Pakistan. However, there are limited published petrophysical data sets on these carbonate rocks and are essential for field development and risk reduction. To fill this knowledge gap, this study is mainly established to collect the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Stress sensitivity was also conducted to assess the impact of stress on the carbonate rock permeability and pore throat structure under various stress conditions. The net stress is described by Equation ( 6) [28]:…”
Section: Determination Of Klinkenberg Permeability and Stress Sensiti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Stress sensitivity was also conducted to assess the impact of stress on the carbonate rock permeability and pore throat structure under various stress conditions. The net stress is described by Equation ( 6) [28]:…”
Section: Determination Of Klinkenberg Permeability and Stress Sensiti...mentioning
confidence: 99%
“…The variations in the slippage parameters and permeability may be attributed to the heterogeneity in the carbonate rocks and nonuniform pore sizes in the samples under study. Consequently, it is evident that the permeability results could not be reliably calculated using the available empirical correlations, as the carbonate rocks exhibited significant heterogeneity and a variety of pore geometries [28]. The slippage effect in a conventional reservoir core is negligible due to the larger pore radius, and the gas slip factor becomes close to zero.…”
Section: Klinkenberg-corrected Permeability and Gas Slippage Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure characterization of subsurface systems is crucial for determining the permeable regions, petrophysical properties, and associated reservoir quality (Tahmasebi, 2017;Dong et al, 2023). These microstructural petrophysical properties of the rocks control the macroscopic properties and flow behavior (Daigle et al, 2017;Fagbemi et al, 2018;Tahmasebi and Kamrava, 2018), which include the topological and geometrical characteristics (Dong et al, 2017;Abro et al, 2019). In this context, carbonate rocks offer a relatively complex microstructure, which is attributed to a range of factors, including but not limited to multimodal pore radius distribution (e.g., micro-porosity and vugs) and mineral heterogeneity (e.g., the classic case of the Arab-D reservoir, where dolomitization leads to massive heterogeneous lithologies) (Arif et al, 2020;Chandra et al, 2021;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Fossil fuels are a significant contributor to the world energy demand [1][2][3][4][5]. It is reported that carbonate reservoir rock formations exhibit a high volume of about 60% of all the global reserves.…”
Section: Introductionmentioning
confidence: 99%